(untitled) (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has rapidly advanced into high-risk domains including healthcare, criminal justice, defense, finance, and autonomous mobility. As AI decision-making systems assume increasing operational authority, the demand for explainability, transparency, and accountability has intensified. Despite superior predictive performance, conventional AI models—particularly deep neural architectures—remain opaque, generating concerns regarding bias, ethical assignment of responsibility, compliance, and public trust. This research explores Explainable AI (XAI) as an accountability enabling framework in high-risk automated ecosystems. The study evaluates algorithmic decision traceability, legal responsibility hierarchies, human-AI interpretability boundaries, and systemic risks under autonomous operations. Using a multi-method empirical approach incorporating stakeholder surveys (n=450), case evaluations across sectors, performance benchmarking of XAI interpretability models, and accountability trace mapping via decision dependency graphs, the study reveals significant gaps in human-auditability, responsibility assignment, model uncertainty communication, and legal liability scope. The research proposes a new framework named TRACE (Transparent, Responsible, Auditable, Cognitive, and Explainable AI) for decision-critical AI deployments. Results indicate improved decision comprehension by 62%, reduction of model trust-deficit by 48%, and enhanced accountability mapping accuracy by 71% when TRACE principles are applied. The study concludes that explainability cannot be treated as a technical augmentation alone—it must evolve into a legally enforceable governance layer tightly coupled with human responsibility pathways.